Relasi Makna (Sinonimi, Antonimi, dan Hiponimi) dan Seluk Beluknya - Masduki Masduki (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2013)
Relation of meaning constitutes as semantic relation based on the relationship of one lexem to the others. This relation covers various meaningful relations. In this article the writer tries to highlight that relation of specifically synonymy, antonymy, and hyponymy. Those relation of meanings are generated on their definitions and complications.